2002
DOI: 10.1159/000063800
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Morphine on Oedema and Tissue Concentration of Nerve Growth Factor in Experimental Inflammation of the Rat Paw

Abstract: Injection of carrageenan (1 mg) into the rat hind paw caused a time-dependent increase in paw volume that was maximal 3 h after injection. At this time, the concentration of nerve growth factor (NGF) in the skin of the inflamed paw was more than twofold higher than in the contralateral, non-inflamed paw. Treatment of rats with indomethacin reduced inflammatory oedema by 57%, morphine treatment attenuated oedema by 62%. While indomethacin had no statistically significant effect on the concentration of NGF in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Previous evidence showed a negative interaction between opiates and NGF signaling pathways in primary sensory neurons (34). Conversely, the inflammation-related increase of NGF induced by carrageenan is attenuated by morphine (35). Morphine and other opiates are currently used as analgesics for several types of severe persistent pain, although their use is limited by several drawbacks, including development of tolerance and physical dependence (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evidence showed a negative interaction between opiates and NGF signaling pathways in primary sensory neurons (34). Conversely, the inflammation-related increase of NGF induced by carrageenan is attenuated by morphine (35). Morphine and other opiates are currently used as analgesics for several types of severe persistent pain, although their use is limited by several drawbacks, including development of tolerance and physical dependence (49).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because a functional interaction between NGF and opioid system was reported in experimental models of inflammatory pain (34,35), the possible synergistic effects of the anti-TrkA antibody with opiates, such as morphine and fentanyl, were investigated.…”
mentioning
confidence: 99%
“…The receptors have also been implicated in the inflammatory process; systemically administered morphine reduces edema and plasma extravasation with an unknown mechanism of action (Hargreaves et al, 1988;Joris et al, 1990;Sacerdote et al, 1996;Walker et al, 1996;Alebouyeh et al, 2002;Amann et al, 2002). In the current study, we sought to investigate the role of centrally and/or peripherally located receptors in pain and edema caused by acute inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that systemically administered morphine produces a substantial reduction of inflammagen-induced extravasation (Hargreaves et al, 1988;Joris et al, 1990) and edema (Hargreaves et al, 1988;Joris et al, 1990;Sacerdote et al, 1996;Walker et al, 1996;Alebouyeh et al, 2002;Amann et al, 2002). Furthermore, Sacerdote et al (1996) and Planas et al (1995) observed a proinflammatory effect of the opioid antagonists naltrexone and naloxone, respectively.…”
mentioning
confidence: 99%
“…For example, early reports demonstrated that NGF could reverse edema caused by the injection of carrageenin, serotonin and dextran (Banks et al 1984;Amico-Roxas et al 1989). Later authors called into question this relationship in inflamed skin (Koltzenburg et al 1999;Amann et al 2002). Finally, the injection of NGF into unperturbed skin has been observed to cause rather than reduce edema (Schuligoi and Amann 1998).…”
Section: Introductionmentioning
confidence: 99%